Imagining Others - Maibom, Heidi (Les ateliers de l'éthique / The Ethics Forum, 2010)
It is often argued that the ability to imagine what others think and feel is central to moral functioning. In this paper, I consider to what extent this is true. I argue that neither the ability to think of others as having representational mental states, nor the ability to imagine being in their position, is necessary for moral understanding or moral motivation. I go on to argue that the area in which thinking about others’ thoughts and feelings appears to play the largest role is that of supererogatory actions. Being able to get on well with others seems to be importantly predicated on our ability to think about their thoughts and feelings and being able to take up their perspective. However, when it comes to grosser moral norms and restrictions, such as harm norms, there is little reason to think that thinking about others’ thoughts and feelings plays a central role in understanding such norms or being motivated by them.